2003
DOI: 10.14507/epaa.v11n26.2003
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Theory and Policy in the Educational Treatment of Language Minority Students: Competitive Structures in California

Abstract: For teachers, theories play a central role in guiding the intellectual work that they have chosen to perform. Teachers are guided by both theories which they use to interpret, analyze and take action in their professional worlds. At any given time, teachers may be faced with multiple and competing theoretical perspectives which attempt to influence their classroom practice. In this article, we examine the theoretical and policy-based positions currently competing to shape the nature of educational practice for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 18 publications
3
24
0
Order By: Relevance
“…Several researchers have looked at how these policies influence students and language minority communities in general (Crawford, 1999;Stritikus & Garcia, 2003;Wiley, 2002). Despite this growing knowledge base, there is also a need to understand how these language policies influence teachers as well as how teachers simultaneously respond to and influence the local enactment of such policies.…”
mentioning
confidence: 99%
“…Several researchers have looked at how these policies influence students and language minority communities in general (Crawford, 1999;Stritikus & Garcia, 2003;Wiley, 2002). Despite this growing knowledge base, there is also a need to understand how these language policies influence teachers as well as how teachers simultaneously respond to and influence the local enactment of such policies.…”
mentioning
confidence: 99%
“…Less work has been done on how to build environments that facilitate new or sustained learning for practicing teachers. To date, professional development for teaching EL students has tended to focus on beliefs that teachers hold about EL students and their families, as these beliefs and theories have considerable impact on the manner in which teachers create (or limit) learning opportunities (Orellana, 1995;Stritikus & Garcia, 2003). In addition, some professional development for working with EL students has focused on changing instructional practices to make them more EL-responsive, and specific "packaged" models (e.g., Guided Language Acquisition Downloaded by [Florida Atlantic University] at 08:33 17 November 2014 Design [GLAD] or Sheltered Instructional Observation Protocol [SIOP] 3 ) have been developed to offer practicing teachers an initial set of tools.…”
Section: Conditions That Support Teacher Learningmentioning
confidence: 99%
“…Although the present study did not examine the degree to which language policies are adhered to in classrooms, others have illustrated the relationship between formal policies and the operational curriculum. Stritikus and Garcia (2003), for example, found that whereas English only policies in California served as justification for personal beliefs for some teachers, others circumvented the curriculum to provide students with native language support. Despite the fact that some teachers will deliver instruction that may not be consistent with policies, there is evidence that there was substantial press for Arizona teachers to comply with Proposition 203.…”
Section: Evidence Of Disparate Ell Models Across Districtsmentioning
confidence: 99%